Effect of Macroeconomic Variables on Jakarta Composite Index before and the Time of Covid19 - et. al., Lia Amaliawiati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study is to examine the effect of macro-economic variables on the Jakarta composite index in Indonesia, both in the short and long term before Covid19 and the Covid19 period, as well as to examine whether there is a difference before Covid19 and the Covid19 period. Macroeconomic variables include exchange rate (ER), inflation (INF), interest rate (INT) and output growth (IP). This study uses data from the times series for the period 2019.1 to 2020.12 by including dummy variables. The first stage is to test the stationary of the data with the root test unit, and the result is that the data is only stationary in the first and second differences. In addition, the co-integration test between the variables and the results shows a co-integration relationship between the variables so that the model can be analyzed using the Error Correction Model (ECM) to see the short-term balance. The results of the ECM model analysis show that, in the short term, the only macroeconomic variables affecting the Jakarta composite index in Indonesia prior to Covid19 and the Covid19 period are only the exchange rate. In the long run before Covid19, the only ones affecting the Jakarta composite index were the exchange rate, while the eCovid19 period was the rate of exchange and inflation. Other results indicate that there is a difference in the average.